Chemical Indices and Kinetic Evaluation of β-Sitosteryl Oleate Oxidation in a Model System of Bulk Oil - Manat Chaijan; Worawan Panpipat; Ling-Zhi Cheong (Molecules, 2022)
Concerns have been raised about the safety and tolerability of phytosterol esters due to their vulnerability to oxidation. Herein, oxidation of the unsaturated fatty acid-phytosterol ester, namely β-sitosteryl oleate, was observed in comparison to native β-sitosterol after accelerated storage at 65 °C for 35 days in a bulk oil model system. Depending on the sterol structure, various chemical indices of lipid oxidation, including hydroperoxide value (HPV), thiobarbituric acid reactive substances (TBARS), p-anisidine value (AnV), and 7-keto derivatives, changed at varying rates in both samples. Such indicators for β-sitosteryl oleate appeared to be obtained at higher concentrations than those for β-sitosterol. The first order kinetic was used to describe the losses of β-sitosteryl oleate and β-sitosterol in bulk oil. It was discovered that the β-sitosteryl oleate (k = 0.0202 day−1) underwent oxidative alteration more rapidly than β-sitosterol (k = 0.0099 day−1). Results indicated that physical structure was the principal factor in the determination of storage stability of phytosterol and its ester. Research on antioxidants and storage techniques can be expanded in order to reduce the oxidative loss of phytosterol esters during storage and improve the safety and tolerability of phytosterol esters.